1998
DOI: 10.1007/s001040050559
|View full text |Cite
|
Sign up to set email alerts
|

Therapie der dislozierten Calcaneusgelenkfraktur mit der AO-Calcaneusplatte

Abstract: patients with 71 displaced intraarticular calcaneal fractures were prospectively examined after an operative treatment using an extended lateral approach and the ASIF calcaneal plate followed by early functional postoperative treatment (mean follow-up 25 months, retrieval rate 96 %). To classify the type of fracture and to verify the results of reduction and of retention CT scans in the coronal and transverse plane were performed pre-and postoperatively and on the day of assessment. The Zwipp Score was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
14

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
3
22
0
14
Order By: Relevance
“…Our group has expanded this reduction method to Type IIA and IIB fractures with the additional use of subtalar arthroscopy to control joint reduction [16,30] in order to reduce the risk of inadequate reduction of the posterior facet with all its potential drawbacks. As biomechanical and clinical studies have consistently shown, even minor step-offs in the joint surface of 1 to 2 mm lead to load redistribution within the posterior joint facet of the calcaneus [24,34], inferior functional scores, and a higher rate of posttraumatic subtalar arthritis [2,4,10,29,33,41]. In our experience, anatomic reduction cannot be achieved with percutaneous methods alone in the majority of calcaneal fractures due to the deep impaction of the posterior facet fragment into the calcaneal body, multiple fragmentation, and interposition of debris and small fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has expanded this reduction method to Type IIA and IIB fractures with the additional use of subtalar arthroscopy to control joint reduction [16,30] in order to reduce the risk of inadequate reduction of the posterior facet with all its potential drawbacks. As biomechanical and clinical studies have consistently shown, even minor step-offs in the joint surface of 1 to 2 mm lead to load redistribution within the posterior joint facet of the calcaneus [24,34], inferior functional scores, and a higher rate of posttraumatic subtalar arthritis [2,4,10,29,33,41]. In our experience, anatomic reduction cannot be achieved with percutaneous methods alone in the majority of calcaneal fractures due to the deep impaction of the posterior facet fragment into the calcaneal body, multiple fragmentation, and interposition of debris and small fragments.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from numerous studies with large patient cohorts that anatomic restoration of the calcaneal shape and joint congruity predict higher functional scores [2-4, 10, 29, 32, 37, 41, 46] and a lower incidence of posttraumatic subtalar arthritis with potentially less need of secondary subtalar fusion [4,24,29,31,33,45] when treating these injuries. However, minor and major wound complications remain a major concern because of the thin and vulnerable skin over the lateral calcaneal wall, which is exposed during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Aber auch die Therapie von Wundrandnekrosen bzw. infizierten Osteosynthesen nach geschlossenen Frakturen [4,6,20] erfordert ggf. das komplette chirurgische Repertoire vom Débridement bis zum Lappentransfer, obwohl durch die Zugangsmodifikationen die Rate der Wundrandnekrosen und sekundärer Infektionen reduziert werden konnten [5].…”
Section: Diskussionunclassified
“…Diese Entwicklung hat zweifelsfrei eine deutliche Verbesserung der Behandlungsergebnisse bewirkt. Gute und sehr gute Ergebnisse werden bei einfachen Frakturtypen in großen Serien mit einer Häufigkeit von 73-82% angegeben [3,19,25]. Frakturtypunabhängig ist mit etwa 61% guten Resultaten zu rechnen [24].…”
Section: Kalkaneusfraktur · Lebensqualität · Ergebnisbewertungunclassified
“…In anderen großen Serien, in denen dasselbe Klassifikationssystem angewendet wurde, findet sich für diesen Frakturtyp ein Anteil von 23 bzw. 52% [3,25]. Weiterhin dürfte die erwiesenermaßen langsam ansteigende Lernkurve für die insgesamt schlecht ausfallenden Ergebnisse mitverantwortlich sein [20].…”
Section: Mittelwerte (± Standardabweichungen) Der Sf-36-skalen Der Aunclassified